The Automatization Method of Processing of Flexible Parts without their Rigid Fixation. (2015) - Filaretov, Vladimir; Zuev, Alexander; Yukhimets, Dmitry; Gubankov, Anton; Mursalimov, Eduard
Abstract: This paper presents a new advanced approach for automatization of processing of flexible parts with arbitrary geometrical forms. This approach based on using multilink manipulators with vision system and allows to exclude the individual equipment for rigid fixing of processed parts. This is achieved by formation and correction of program motions of cutting tool of manipulator using information about current position of processed parts from 3D vision system.